2009
DOI: 10.1016/j.juro.2009.02.132
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bladder Urine Transforming Growth Factor-β1 Concentrations in Diagnosis and Management of Unilateral Prenatal Hydronephrosis

Abstract: Bladder urine transforming growth factor-beta1 changes through time are associated with similar changes in hydronephrosis grade. Bladder urine transforming growth factor-beta1 in the first 3 months of life can predict the need for surgery in newborns with prenatal hydronephrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
0
18
1
7
Order By: Relevance
“…This type of abnormal anatomy is often found in children with the VACTERL association or cloacal anomalies. Non-invasive studies such urinary biomarkers such as transforming growth factor beta are still under investigation, but hold promise in predicting those cases who would deteriorate and require closer follow-up (37). Similarly, the field of functional renography holds promise both with nuclear medicine (38) and positron emission tomography (39).…”
Section: Ancillary Testsmentioning
confidence: 99%
“…This type of abnormal anatomy is often found in children with the VACTERL association or cloacal anomalies. Non-invasive studies such urinary biomarkers such as transforming growth factor beta are still under investigation, but hold promise in predicting those cases who would deteriorate and require closer follow-up (37). Similarly, the field of functional renography holds promise both with nuclear medicine (38) and positron emission tomography (39).…”
Section: Ancillary Testsmentioning
confidence: 99%
“…Biomarkers are potentially useful diagnostic tools, which have recently become a focus of clinical research [9][10][11][12][13]. Regarding the pediatric nephrourology setting, there have been various attempts to identify noninvasive diagnostic markers of congenital renal obstruction and vesicoureteral reflux (VUR) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Galanakis et al [18] have found elevated urinary IL-8 concentration in infants with VUR. Recently, Almodhen et al [9], observed that a cutoff of 17 pg/mmol creatinine for bladder TGF-β1 levels collected in the first 3 months of life had a good diagnostic accuracy in predicting surgery in patients with unilateral prenatal hydronephrosis. Drecramer and co-workers [19] and, more recently, Drube et al [20] have shown that novel non-invasive proteomic urine tests predict with high accuracy the need for surgery in infants with ureteropelvic junction obstruction (UPJO).…”
Section: Introductionmentioning
confidence: 99%
“…Em estudos clínicos, também se observou a correlação positiva dos níveis do TGF ß1 com uropatia obstrutiva, com aumento dos níveis urinários de TGF ß1 em crianças com estenose da junção ureteropiélica submetidas à pieloplastia (Palmer et al, 1997;Furness et al, 1999;El-Sherbiny et al, 2002;Sager et al, 2009;Almodhen et al, 2009). …”
Section: Discussionunclassified
“…Ratos transgênicos adultos Klotho, que são portadores de proteína Klotho, submetidos à UUO, tiveram supressão dos efeitos do TGF ß1, incluindo diminuição da transição epitelial-mesenquimal, diminuição da resposta inflamatória associada à obstrução e da subsequente fibrose renal. Houve inibição da fosforilação da Smad2 (Doi et al, 2011 Além disso, reforçou-se a idéia de que o TGF ß1 urinário é uma ferramenta não invasiva útil após a pieloplastia (Almodhen et al, 2009). …”
Section: Tgf-β1unclassified